Efficiency improvement of a-Si:H Thin-Film Solar Cells by phosphorus doping of absorption layer with a-Si:H buffer layer at p/i interface. (22nd November 2018) - Son, Won Ho; Lee, Si-Hun; Kim, Jae Keon; Choi, Sie Young; Kong, Seong Ho; Jung, Daewoong
Abstract: Comparative properties of pin-type amorphous silicon (a-Si:H) thin-film solar cells with different PH3 flows for the i-layer and the presence of a buffer layer at the p–i interface were investigated. Doped a-Si:H films with different PH3 concentrations were fabricated by mixing PH3, SiH4, and H2 during i-layer deposition. The flows were changed within 0–4.2 sccm, the total thickness of the buffer and intrinsic layers was 200 nm, and the thickness of the buffer layer was varied from 0–30 nm. All amorphous materials on films were deposited by a plasma-enhanced chemical vapor deposition method. Output performances (open-circuit voltage Voc, short-circuit current density Jsc, fill factor FF, and conversion efficiency η) of the solar cells were characterized to optimize the structural features and manufactural processes. The maximum values of parameters were measured at a PH3 flow of 0.9 sccm. Excessive or insufficient flow rates of PH3 will deteriorate the solar cell characteristics because of the resulting large defect density and increased recombination rate, respectively. Performance of solar cells with the a-Si:H buffer layer (Voc = 0.682V, Jsc = 17.21 mA/cm 2, FF = 0.51, and η = 6.03) improved compared with the results where phosphorus was lightly doped on the i-layer of pin-type a-Si:H solar cells without a buffer layer (Voc = 0.655 V, Jsc = 17.08 mA/cm 2, FF = 0.46, and η = 5.11).